Detection and characterization of quantitative trait loci for phytic acid in grains toward improved black rice in northern Laos - Toshiyuki Takai; Hiroki Saito; Junichiro Marui; Aung Zaw Oo; Koukham Vilayheuang; Sengthong Phongchanmixay; Hidetoshi Asai (Frontiers in Sustainable Food Systems)
Black rice is an essential agricultural commodity in the upland ecosystems of northern Laos. Considering the low yield potential of black rice and the low-fertility soils in the region, breeding improved black rice with high yield potential and phytic acid (PA) content in grains as a phosphorus source for vigorous seedling growth is necessary. This study included genetic analyses conducted in Laos and Japan using an F2 population derived from a cross between Kampeng, a black rice variety with a high PA content, and Non, a white rice variety with more panicles, even in low-fertility soils. A major quantitative trait locus (QTL) for grain color was detected in Kala4, which is involved in the expression of the black color in the rice variety. Two QTLs were detected for PA content. One of these, a novel QTL named qPA1, was detected at the end of the short arm of chromosome 1 in both Japan and Laos. The effect of the Kampeng allele on increasing the PA content was demonstrated in the F3 lines. An additional QTL identified exclusively in Japan was suggested to be due to an environmental response via Hd6. PA accumulation in late-heading F2 individuals by Hd6 may have been suppressed due to low temperatures. In addition, no QTLs were detected for the Non allele that increased the panicle number, although Non exhibited more panicles than Kampeng. These results indicate that incorporating the Kampeng allele of Kala4 and qPA1 into the Non genetic background may serve as an effective breeding strategy. This approach could enhance the development of black rice with high yield potential and PA content, thereby contributing to increased black rice production in the upland ecosystems of northern Laos.